Peningkatan Efektivitas Belajar Futsal dengan Modifikasi Gaya Siswa Kelas VI Sekolah Dasar - Basri Basri (Graduate School of Universitas Negeri Malang, 2018)
Abstract: This study aims to determine the increase in futsal learning by modifying the style of sixth grade elementary school students. The research conducted was a two-cycle class action research. Each cycle is carried out in the form of a mixed assessment process consisting of four stages namely, planning, implementation, observation, and reflection. The research objectives were students of class VI.B semester 12 of 020 Samarinda Ilir State Elementary School. Based on the analysis, the results of the study showed an increase in the value of student activity in the futsal learning process with an average of 75.6% and classified in the active category. In addition, an increase also occurred in the teaching activities of teachers with an average value of 97.5% active and classified in the very active category. Finally, students' mastery learning also increased after treatment in the second cycle followed by a response that showed students were happy with the style modification learning by the teacher.Abstrak: Penelitian ini bertujuan untuk mengetahui peningkatan belajar futsal dengan modifikasi gaya siswa kelas VI sekolah dasar. Penelitian yang dilakukan merupakan penelitian tindakan kelas sebanyak dua siklus. Setiap siklus dilaksanakan dalam wujud proses pengkajian berdaur yang terdiri atas empat tahap yakni, perencanaan, pelaksanaan, observasi dan refleksi. Sasaran penelitian adalah siswa kelas VI.B semester 12 Sekolah Dasar Negeri 020 Samarinda Ilir. Berdasarkan analisis didapatkan hasil penelitian berupa peningkatan nilai aktivitas siswa pada proses pembelajaran futsal dengan rata-rata 75,6% dan tergolong dalam kategori aktif. Selain itu, peningkatan juga terjadi pada aktivitas mengajar guru dengan rata-rata nilai keaktifan 97,5% dan tergolong pada kategori sangat aktif. Terakhir, ketuntasan belajar siswa juga meningkat setelah dilakukannya treatment pada siklus II diikuti respon yang ditunjukkan siswa merasa senang dengan pembelajaran modifikasi gaya oleh guru.